2010
DOI: 10.1128/jcm.02306-09
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of Veterinary Yeast Isolates by Use of Sequence-Based Analysis of the D1/D2 Region of the Large Ribosomal Subunit

Abstract: Conventional methods of yeast identification are often time-consuming and difficult; however, recent studies of sequence-based identification methods have shown promise. Additionally, little is known about the diversity of yeasts identified from various animal species in veterinary diagnostic laboratories. Therefore, in this study, we examined three methods of identification by using 109 yeast samples isolated during a 1-year period from veterinary clinical samples. Comparison of the three methods-traditional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 44 publications
2
17
0
1
Order By: Relevance
“…Macroconidia were formed after [4][5][6][7] days from short multi-branched conidiophores which may form sporodochia. They are 3-septate, fusiform, cylindrical, often moderately curved, with an indistinctly pedicellate foot cell and a short blunt apical cell, (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) 毺m 暳 4-6 毺m). Microconidia are usually abundant, cylindrical to oval, oneto two-celled and formed from long lateral phialides, (8)(9)(10)(11)(12)(13)(14)(15)(16) 毺m 暳 2-4.5 毺m).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Macroconidia were formed after [4][5][6][7] days from short multi-branched conidiophores which may form sporodochia. They are 3-septate, fusiform, cylindrical, often moderately curved, with an indistinctly pedicellate foot cell and a short blunt apical cell, (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) 毺m 暳 4-6 毺m). Microconidia are usually abundant, cylindrical to oval, oneto two-celled and formed from long lateral phialides, (8)(9)(10)(11)(12)(13)(14)(15)(16) 毺m 暳 2-4.5 毺m).…”
Section: Resultsmentioning
confidence: 99%
“…It has typically been most useful for molecular systematics at the species level, and even within species (e.g., to identify geographic races). Because of its higher degree of variation than other genic regions of rDNA (for small-and large-subunit rRNA), ITS has proven especially useful for elucidating relationships among congeneric species and closely related genera in clinically important yeast species [35] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeast identification was based on assessment of macroscopic and microscopic features and nutrient assimilation using API 20 C AUX test strips b or the Uni-Yeast-Tek system c . Yeast differentiation methods were expanded to include fatty acid profile analysis in 2007 and DNA sequencing in 2009 [3]. The DNA sequencing revealed that many of the genus and species designations assigned to yeast isolates before 2009 were imprecise (Dr C. Altier, personal communication).…”
Section: Methodsmentioning
confidence: 99%
“…The incidence of fungal infection in mares diagnosed with endometritis is significantly lower than the incidence of bacterial infection but fungal endometritis is more challenging to treat and carries a guarded-to-poor prognosis for future fertility [1][2][3][4][5][6][7][8][9][10][11][12]. Suggested doses and treatment regimens for fungal endometritis are mostly based on case studies or extrapolations from other species (Tables S1-S3).…”
Section: Introductionmentioning
confidence: 99%